Successful venoarterial extracorporeal membrane oxygenation for prolonged hepatopulmonary syndrome following pediatric liver transplantation: A case report and review of the literature. (19th August 2017) - Khan, Hamza Hassan; Schroeder, Laura; Fitzpatrick, Megha S.; Kaufman, Stuart S.; Yazigi, Nada A.; Yurasek, Gregory K.; Steinhorn, David M.; Fishbein, Thomas M.; Khan, Khalid M.
Abstract: HPS is a major complicating feature of end‐stage liver disease. Diagnosis is clinical, and LT is the only definitive treatment. While the general impression is that HPS improves quickly after transplantation, it may not always be the case. We describe the smallest reported child with HPS prior to LT and requiring prolonged venoarterial extracorporeal membrane oxygenation after LT; especially as it is a rare occurrence, physician managing such cases should be aware of the circumstances under which HPS may require specific treatment.